Teaching quality management of physical education specialty in China and Ukraine - Liang Zhang; Pei Diao (Institute of Advanced Engineering and Science, 2023)
The integration of quality management in physical education has changed the traditional approach to teaching. The information overload and an enormous amount of irrelevant data available to qualified specialists may lead to professional stress. Quality management offers educators tips on how to avoid information overload while still staying updated with the necessary information, knowledge and skills. The research aimed to examine the main characteristics of quality management in teaching. The sample consisted of 296 students: 73% - male subjects, 27% - females subjects. The average age is 19.37±0.31. The research analyzed the factors affecting the quality of education using the quality competency and student satisfaction questionnaire. The findings revealed that Chinese students were satisfied with the physical and environmental conditions (8.1±0.23 points) and it was 22% higher than the results of Ukrainian students. The education programs, technological opportunities and student scientific work have the greatest influence on the quality of education in China (8.38±0.32). The least influence has the adequacy of management and staff (7.21±0.27). Career support, tours and practices related to physical education have the greatest influence on the education quality in Ukraine (8.43±0.32). The parameters identified by the research can be integrated into the system of higher physical education to improve the quality and academic achievements.